Дослідження по гетерогенному кислотно-основному каталізу в Інституті сорбції та проблем ендоекології НАН України - Brei, Volodymyr V. (Каталіз та нафтохімія, 2023)
In chronological order, the reaseach results of Department of heterogeneous acid-base catalysis at Institute for sorption and endoecology problems in 2003-2023 are described. It relates to the synthesis, study and application of solid superacids WO3/ZrO2, WO3/ZrO2-SiO2, ZrO2-SiO2-Al2O3, ZrO2-SiO2-SnO2, as catalysts, in vacuum gas oil cracking, alkylation of isobutane with isobutanol, acylation toluene, oligomerization of tetrohydrofuran, acylation of methyl tert-butyl ether and other. Some study deals with a search of the correlations between of acid site strength of a catalyst and its activity, in particular, in dehydration reaction of C2-C4 alcohols, and the correlations between ability of primary and secondary alcohols to dehydrogenation and oxidation and their chemical shifts δ (R17OH) and δ (R13СОH ). For the first time, the values of Hammett's acidity function have been measured at elevated (up to 200 °C) temperatures for solid acids. In particular, for H-Y faujasite, H0 reaches superacidic value H0 at 160 °С. Since 2010, the main focus has been on the catalytic conversion of renewable raw materials, mainly bioalcohols (ethanol, glycerol) and C6 carbohydrates, into important products of organic synthesis (ethyl acetate, 1,1 diethoxyethane, n-butanol, propylene glycol, alkyl lactates, lactide, glycolide). In cooperation with “Techinservice Manufacturing Group”, new processes for obtaining ethyl acetate, 1,1 diethoxyethane, n-butanol from bioethanol and racemic lactide from glycerol were developed. Also, new technologies for obtaining propylene oxide from propylene and hydrogen peroxide (НРPОа-process), vapor phase hydrogenation of the pyrolysis C4-5 fraction, and direct high-temperature chlorination of ethylene to vinyl chloride have been developed for Kalush “Karpatnaftochim” plant. The HHPOa installation (2000 t/y) has been started at “Karpatnaftochim” in 2020.